On bonded Indian and uniformly parallel insertion systems and their generative power - Yosman, Ahmad Firdaus; Holzer, Marcus; Truthe, Bianca; Fong, Wan Heng; Turaev, Sherzod (Penerbit UTM Press, UTM, 2017)
Insertion is an operation in formal language theory that generalizes the operation of concatenation of words, where its variants allow the operation in different ways. Parallel insertion is a variant of insertion that simultaneously adds words between all letters of a word and also at the right and left extremities. In previous research, restrictions on the applicability have been imposed leading to so called bonded insertion systems with a sequential and a parallel variant. Motivated by the atomic behavior of chemical compounds in the process of chemical bonding, the generative power of bonded insertion systems has been investigated where a language hierarchy was obtained. In this paper, we introduce new variants of bonded parallel insertion systems, namely bonded Indian parallel insertion systems and bonded uniformly parallel insertion systems. We present some results regarding the generative power of these new systems and a language hierarchy.